Enhanced Photocatalytic Paracetamol Degradation by NiCu-Modified TiO2 Nanotubes: Mechanistic Insights and Performance Evaluation - Pinna, Marco; Zava, Martina; Grande, Tommaso; Prina, Veronica; Monticelli, Damiano; Roncoroni, Gianluca; Rampazzi, Laura; Hildebrand, Helga; Altomare, Marco; Schmuki, Patrik; Spanu, Davide; Recchia, Sandro (Nanomaterials, 2024)
Anodic TiO2 nanotube arrays decorated with Ni, Cu, and NiCu alloy thin films were investigated for the first time for the photocatalytic degradation of paracetamol in water solution under UV irradiation. Metallic co-catalysts were deposited on TiO2 nanotubes using magnetron sputtering. The influence of the metal layer composition and thickness on the photocatalytic activity was systematically studied. Photocatalytic experiments showed that only Cu-rich co-catalysts provide enhanced paracetamol degradation rates, whereas Ni-modified photocatalysts exhibit no improvement compared with unmodified TiO2. The best-performing material was obtained by sputtering a 20 nm thick film of 1:1 atomic ratio NiCu alloy: this material exhibits a reaction rate more than doubled compared with pristine TiO2, enabling the complete degradation of 10 mg L−1 of paracetamol in 8 h. The superior performance of NiCu-modified systems over pure Cu-based ones is ascribed to a Ni and Cu synergistic effect. Kinetic tests using selective holes and radical scavengers unveiled, unlike prior findings in the literature, that paracetamol undergoes direct oxidation at the photocatalyst surface via valence band holes. Finally, Chemical Oxygen Demand (COD) tests and High-Resolution Mass Spectrometry (HR-MS) analysis were conducted to assess the degree of mineralization and identify intermediates. In contrast with the existing literature, we demonstrated that the mechanistic pathway involves direct oxidation by valence band holes.
CRIS-Team Scopus Importer:2024-10-25
Keywords: emerging pollutants; green chemistry; heterojunction; NiCu bimetallic catalysts; paracetamol; photocatalysis; TiO; water remediation